2017
DOI: 10.1155/2017/7639084
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA in Glioblastoma: An Overview

Abstract: Glioblastoma is the most aggressive brain tumor and, even with the current multimodal therapy, is an invariably lethal cancer with a life expectancy that depends on the tumor subtype but, even in the most favorable cases, rarely exceeds 2 years. Epigenetic factors play an important role in gliomagenesis, are strong predictors of outcome, and are important determinants for the resistance to radio- and chemotherapy. The latest addition to the epigenetic machinery is the noncoding RNA (ncRNA), that is, RNA molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
118
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(121 citation statements)
references
References 210 publications
(201 reference statements)
0
118
0
3
Order By: Relevance
“…Recent studies have highlighted the pivotal roles of miRNAs in regulating GBM development and their potential as targets for cancer therapy . In order to reveal the regulatory mechanism of HMGB3 in GBM, we first sought to determine whether any relevant miRNAs regulate HMGB3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have highlighted the pivotal roles of miRNAs in regulating GBM development and their potential as targets for cancer therapy . In order to reveal the regulatory mechanism of HMGB3 in GBM, we first sought to determine whether any relevant miRNAs regulate HMGB3.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have highlighted the pivotal roles of miRNAs in regulating GBM development and their potential as targets for cancer therapy. 26 In order to reveal the regulatory mechanism of HMGB3 in GBM, we first sought to determine whether any relevant miRNAs regulate HMGB3. Using the miRNA target prediction algorithm TargetScan (www.targetscan.org), we determined that HMGB3 was a predicted target of miR-200b-3p and miR-200c-3p ( Figure 5A).…”
Section: Hmgb3 Is Targeted By Mir-200b-3p and Mir-200c-3pmentioning
confidence: 99%
“…miRNAs are small non-protein-encoding RNAs which have been shown to be involved in cancer progression (Lu et al, 2005). Previous studies have shown that miRNAs can regulate glioma progression (Banelli et al, 2017;Shea et al, 2016), which makes miRNA a possible target for drug development in glioma. In the meanwhile, miRNAs and lncRNAs can also involve in the lncRNA-miRNA regulatory network to regulate cancer progression (Liz & Esteller, 2016 regulate renal carcinoma (Chiyomaru et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are small, noncoding RNAs that regulate gene expression preferentially by binding to the 3′‐untranslated region (3′‐UTR) of mRNAs in a sequence specific manner, thereby leading to inhibition of translation and/or enhanced mRNA degradation . Altered miRNA expression, including down‐regulation of tumour suppressive and up‐regulation of tumour promoting miRNAs, have been identified in many cancers , including gliomas . Among the first miRNAs implicated as tumour suppressors was miR‐16‐5p , which belongs to a family of evolutionary conserved miRNAs that share a common seed sequence.…”
Section: Introductionmentioning
confidence: 99%